Investigations of velocity and pressure fluctuations over a stepped spillway with new step configuration - Udai A. Jahad; Riyadh Al-Ameri; Subrat Das (Water Supply, 2022)
The effect of the end sill shape of steps for two-phase flow over stepped spillways was investigated. A quantitative assessment approach has been applied. Experimental and numerical tests were used for stepped spillways with different step configurations. The computational fluid dynamics (CFD) method with a two-dimensional (2D) flow model, including volume of fluid (VOF) and k-ε models was applied to conduct a critical analysis in different flow conditions. Step heights hs were 0.03 m and 0.05 m, and the number of steps Ns were 10 and 6, respectively. The step configurations assessed were Step models, Sill models, and Curve models with angle θ = 26.6°. The developed 2D model investigated the flow patterns, velocity distribution, and pressure for several step configurations. For validation, the correlation coefficient (R), mean absolute percentage error (MAPE), and root mean squared error (RMSE) were tested. The results showed negative pressure at the flat steps at Nappe flow, whilst negative pressure did not appear in the Curve model. MAPE and RMSE were 4.32 and 0.21 respectively, with R =0.996. In the CFD results, velocity and the pressure distributions were compared with the experiments and showed a correlation within a (±6%) tolerance. The Curve models were the best in terms of the flow characteristics. HIGHLIGHTS Flow regimes were simulated for different flow conditions along the stepped spillway.; The velocity distribution was simulated at the first step, mid-step, and last step.; The pressure distribution was simulated for nappe and skimming flow at the first step, mid-step, and last step.; The water surface profile with flow streamlines were simulated along the stepped spillway.;